Hadis tentang Keutamaan Shalat Berjamaah - Muhammad Ilyas (Jurnal Riset Agama, 2021)
The purpose of this study is to discuss the traditions about the virtues of praying in congregation. This research method uses qualitative type through literature study using content analysis. The results and discussion of this study include general views of prayer in congregation, traditions about prayer in congregation, and the commandment of prayer and its virtues. The conclusion of this study is to find out how important prayer is in congregation, because prayer is the pillar of religion. Whoever establishes the prayer establishes his religion, and whoever abandons the prayer destroys his religion. This research is expected to be able to open up the views of parents so that in educating children it should not only be in terms of science, but must be accompanied by spiritual knowledge, one of which is prayer.